Curumim e Cunhatã Surdos em Cordéis Sim Senhor? Criação de uma obra sobre a perspectiva de uma discente sobre os artefatos culturais da comunidade surda. - Santos, Deborah Rodrigues da Costa (Brasil, 2022)
Literature and Culture, if observed in detail, have points that determine the relationship of emergence of identities of the being itself, the work proposes to present the details of how the cultural artifacts of the Deaf Community are important for the construction of deaf identities and the identification of their own culture. By choosing to present the work “Curumim e Cunhatã Surdos em Cordéis Sim Senhor@” from the perspective of writing questions related to the importance of building identities through cultural artifacts and their linguistic development, collaborating with deaf leadership in subjectivity when common experiences produce cultural artifacts. The author requires expressing through this work the importance of how these cultural artifacts produce in themselves the construction of the deaf subject's identity and subjectivity. For the creation of this work, the author sought to focus on studies on the deaf culture of Strobel 2008, where the researcher and author of the book “The images of the other on deaf culture”, writes about the cultural artifacts of the deaf community, a book used to study and creation of the work Curumim and Cunhatã Surdos in Cordéis Sim Senhor.